Recent advances in conventional and innovative extraction techniques for recovery of high-added value compounds for food additives and nutraceuticals - Abhishek Bisht; Subash Chandra Sahu; Anand Kumar; Sammra Maqsood; Mukul Machhindra Barwant; Swapnil G. Jaiswal (Food Physics)
There is a growing interest in the extraction of high-value compounds in food processing and industrial applications due to a need to enhance the quality, nutritional aspect, and appeal of the final product. This review critically examines traditional and emerging extraction technologies against their efficiency, environmental sustainability, scalability, and stability of the compounds extracted. Advanced methods include pulsed electric field extraction, enzyme-assisted extraction, and microwave-assisted extraction whose application can enhance the bioavailability, oxidative stability, and antioxidant potential of bioactive compounds above traditional methods. Special attention is paid to innovative developments in methods of extraction and their specific applications in food additives and dietary supplements. We discuss the implications of these high technologies in current industry practice, health benefits for consumers, and in the environment with regard to sustainability, thus giving a preview of the transformative changes that will take place in extraction technologies in the food sector.